THE RELEVANCE OF ISLAMIC EDUCATION (PAI) LESSON PLANNING TO THE ENHANCEMENT OF STUDENTS' CHARACTER - Masruroh, Siti; Sasmita, Mitra; Zainuri, Rahma Dilla; Rahmatiani, Lusiana; Ali, Agus (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The purpose of this study on the relevance of Islamic Education (PAI) lesson planning to the enhancement of students' character is to foster students' awareness of the importance of character values embedded within themselves. This research employs field research methodology, which involves collecting data directly from the research location. To support the success of the study, a relevant approach was used, specifically a qualitative descriptive method for this analysis.The findings indicate that the overall PAI learning system at SMK Jayabeka 01 Karawang demonstrates a strong relevance between the planning, implementation, and objectives of the lessons with students' character values. This alignment supports the achievement of students with exemplary character, well-prepared to face the professional world. In conclusion, PAI lesson planning plays a crucial role in instilling faith, piety, and character values in students, aligning with educational goals and the school's vision and mission. By designing structured syllabi, lesson plans, methods, and evaluations, PAI teachers contribute to shaping students with noble character, confidence, independence, and curiosity. The learning process is enhanced through innovative approaches, such as interactive media and group discussions, creating an effective and enjoyable learning environment. Supporting factors include students' freedom to express opinions, relevant learning media, and good communication between teachers and students. However, challenges such as uneven religious understanding and Qur'an reading abilities require additional intervention from teachers and parental support.